Investigation of tool wear resistance when smoothing parts - Marchenko, D.D.; Matvyeyeva, K.S. (Problems of Tribology, 2020)
The article discusses the method of surface plastic deformation of steel parts by smoothing. The positive influence of this method on the wear resistance of the tool has been established under conditions of intense wear and with abundant lubrication